HYPOGLYCAEMIC EFFECT OF SYZYGIUM CARYOPHYLLATUM (L.) ALSTON ON ALLOXAN INDUCED DIABETIC ALBINO MICE - RABEQUE, C. SAVITHA; PADMAVATHY, S. (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: The primary objective of this study was to determine the hypoglycaemic activity of S. caryophyllatum in alloxan induced diabetic mice. Methods: Alloxan was administered as a single dose (60mg/kg, b. wt) to induce diabetes. Methanol extracts from S. caryophyllatum (250mg/kg body weight/day) was administered for 14 days to alloxan induced diabetic mice and the body weight changes and fasting blood sugar levels were monitored on 0, 7th and 14th day. Glycosylated haemoglobin levels also estimated. Â Result: The results suggest that the administration of S. caryophyllatum have hypoglycaemic activity in alloxan induced diabetic mice and their effect was equivalent to that of reference drug Glibenclamide. Conclusions: The results suggested that the methanol extract of S. caryophyllatum Â possess anti-diabetic effect on Alloxan induced diabetic mice and it can be recommended for the prevention of diabetes mellitus. Keywords: Alloxan monohydrate, Glibenclamide, Glycosylated haemoglobin